2014
DOI: 10.1128/aem.01620-14
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas putida Strain Genetically Engineered for 1,2,3-Trichloropropane Bioremediation

Abstract: c 1,2,3-Trichloropropane (TCP) is a toxic compound that is recalcitrant to biodegradation in the environment. Attempts to isolate TCP-degrading organisms using enrichment cultivation have failed. A potential biodegradation pathway starts with hydrolytic dehalogenation to 2,3-dichloro-1-propanol (DCP), followed by oxidative metabolism. To obtain a practically applicable TCPdegrading organism, we introduced an engineered haloalkane dehalogenase with improved TCP degradation activity into the DCP-degrading bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…The biodegradation activity of engineered P. putida in spiked soil (autoclaved soil and natural soil containing microbial flora) on oil biodegradation showed oil removal compared to wildtype group was increased statistically significant. In the recent study by Samin et al 2014 genetically engineered P. putida via cloning of dehalogenase gene (dhaA31) generated for evaluation the 1,2,3-Trichloropropane (TCP) degradation activity (36). Same to the findings of the present study PAH compound in oil and chlorinated hydrocarbon can effectively biocatalyst by GEMs.…”
Section: Discussionsupporting
confidence: 60%
“…The biodegradation activity of engineered P. putida in spiked soil (autoclaved soil and natural soil containing microbial flora) on oil biodegradation showed oil removal compared to wildtype group was increased statistically significant. In the recent study by Samin et al 2014 genetically engineered P. putida via cloning of dehalogenase gene (dhaA31) generated for evaluation the 1,2,3-Trichloropropane (TCP) degradation activity (36). Same to the findings of the present study PAH compound in oil and chlorinated hydrocarbon can effectively biocatalyst by GEMs.…”
Section: Discussionsupporting
confidence: 60%
“…Given these abilities, it is no surprise that the solvent tolerant strains of the Pseudomonads are often used for the bioremediation of toxic organic solvents like 1,2,3 trichlorpropane (Samin et al, 2014) or biocatalytic transformations of aromatic hydrocarbons like the epoxidation of styrene (Volmer et al, 2014) (reviewed in (Poblete-Castro et al, 2012)). Strains of the Pseudomonads are also used for the de novo production of aromatic hydrocarbons like p-hydroxybenzoic acid (Verhoef et al, 2007) and p-coumarate (Nijkamp et al, 2007).…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…18 Consequently, the design of enzymes and pathways that would allow organisms to degrade or even recycle TCP was investigated by different groups, with results that convincingly showed that biodegradation can be achieved. 19,20 The results of this work provide insight in the causes of success and failure as well as provide indications for future directions.…”
Section: Introductionmentioning
confidence: 93%
“…The DhaA31 variant 57 was introduced in the 2,3-dichloro-1propanol degrader Pseudomonas MC4 61 using chromosomal integration instead of a plasmid and without co-introduction of an antibiotic resistance marker or plasmid mobilization genes. 20 Insertion into the chromosome looks more attractive for bioremediation applications, and should relieve concerns related to distribution in the environment of genes encoding engineered enzymes or antibiotic resistance proteins. The Pseudomonas MC4 host was obtained earlier by classical enrichment with 2,3-dichloro-1-propanol from a site in the Botlek area mentioned above.…”
Section: Engineering Tcp Degrading Enzymes and Organismsmentioning
confidence: 99%